Orientalism on the Revelation of the Prophet: the Cases of W. Montgomery Watt, Maxime Rodinson, and Duncan Black MacDonald (American Journal of Islam and Society, 1986)
W. Montgomery Watt, Muhammad at Mecca (Oxford: At the Clarendon Press, 1953), 192pp., and Muhammad at Medina (Oxford: At the Clarendon Press, 1956), 417 pp.Maxime Rodinson, Mahomet (France: Club francais du livre, 1961), 378 pp., English translationby Anne Carter Muhammad, (London, The Penguin Press, 1971), with New Introductionand Foreward (New York, Pantheon Books, 1980), 363 pp.Duncan Black MacDonald, Aspects of lslam (New York, The Macmillan Company, 1911), 375 pp.The biography (Sira) of the Prophet Muhammad (SAAW) has attractedthe interest of scholars in both the Islamic world and the West for centuries.Vast literature exists on the subject in Arabic and in numerous European andAsian languages. The reasons for this interest are numerous and complex,ranging from religious to ideological and political motivations. The earliestArabic biographies of the Prophet date back to the second century of the Hijra/eighth century A.C. The Sira of Ibn-Ishaq and that of Ibn-Hisham (basedon the former) have had the greatest influence on the vast literature concerningthe Sira. Yet there are Siras dating back to the sixth and seventh centuriesA.H. which are still in the form of manuscripts waiting to be edited. TheQur‘an and the sayings and actions of the Prophet (Hadith) are the two mostimportant sources for studying the Prophet’s Sira.The Prophet’s biography has attracted great interest also in the West. Duringthe Middle Ages, the Prophet was the object of attack by Christian priestsand propagandists, whom we might call the original Orientalists. He wasdenigrated, his figure was deformed, and he was given insolent names like ...